The Importance of The Role of Parents in Children's Marriages to Get a Major Who is Sekafah and Sekufu In religious and Sema Law Number 2 Year 2023 - Habib, Muhamad; Hantoro, Setyo; Maemunah, Maemunah; Harahap, Sintong Mangandarmuda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Having a partner who shares the same faith, beliefs, and is compatible in terms of kafa'ah (suitability) and kufu (equality) is a dream for every person, especially among Muslims. A marriage with a partner who is aligned in faith, beliefs, kafa'ah, and kufu is believed to foster a harmonious household, free from conflicts that could lead to disputes between husband and wife, potentially resulting in a failed marriage. Therefore, guidance and advice from parents play a crucial role in preparing children to choose a spouse who aligns with their faith, beliefs, and compatibility in kafa'ah and kufu. over time, this concept has developed into several factors such as age, occupation, education, and even religious organizations. Unbalanced couples often lead to disputes between the two. Meanwhile, a balanced couples will greatly assist the socialization process towards family happiness, namely the sakinah, mawaddah and rahmah families.